II–VI Semiconductor-Polymer Nanocomposites and Their Gas-Sensing Properties - Kumar C.; Jit S.; Saxena S.; Shukla S. (My University, 2025)
Hybrid nanocomposites with performance are prepared using II–VI semiconductors and polymers. The II–VI semiconductor-polymer nanocomposite has advantage of both the II–VI semiconductors and polymers. The most important features of II–VI semiconductor nanomaterials are increased surface-to-volume ratio, bandgap modulation and catalytic behaviour. The polymers have the advantage of low-temperature processing and are sensitive to low concentrations of hazardous gases. The conducting polymer has the additional advantage of reducing any void in the thin film of nanostructured II–VI semiconductors. These nanocomposites have some specific advantages, and accordingly, they are used in electronic devices and sensors. Generally, Cd and Zn-based nanomaterials are utilised for the synthesis of nanocomposites for gas-sensing applications. CdSe-polymer and CdS-polymer nanocomposites have been used largely for the fabrication of gas sensors. CdS-polyaniline nanocomposite has shown the highest gas response for nitrogen dioxide gas, whereas maximum gas response is obtained in CdSe-PQT-12 nanocomposite-based sensor. II–VI semiconductor-polymer nanocomposites include advantages such as tailored selectivity, mechanical flexibility, improved long-term stability, etc. The surface modification and selective window for the sensing can improve the lifetime of the nanocomposite-based gas sensors. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.